RECOMBINANT LENTIVIRUS VECTOR TARGETING BOVINE LXRΑ MRNA AND ITS SILENCING EFFECTS ON BOVINE MUSCLE SATELLITE CELLS - Y. Liu; P. Lib; L. Zhao; Z. Zhao; Y. Li; M. Liu; X. Yang; L. Zan (Journal of Animal and Plant Sciences, 2017)
The liver X receptor α (LXRα) is a member of the nuclear hormone receptor superfamily which could regulate the transcription of the genes involved in cholesterol transportation. In this study, Lentiviral vector containing LXRα shRNAs were constructed and transferred in bovine muscle satellite cells. The results indicated that LXRα down regulated PPARα, PPARγ, ABCA1, LPL, ApoE genes after 48 h post-pLenti-03 viruses' infection. The silencing effects of bovine LXRα gene on related were significant. This work identifies bovine LXRα role in cholesterol metabolism.
Keywords: bovine LXRα gene; lentivirus; vector construction; gene silencing